Korelasi Kepemimpinan dengan Komitemen dan Lingkungan Kerja Dosen D3 Kebidanan - Hesty Widyasih; Ma’mun Sutisna; Firman F. Wirakusumah (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2012)
Background: Leadership in midwifery education may bring into positive change such as increase of organization quality. Leadership facilitates to build high working commitment and good working environment. Malcolm Baldrige criteria is a working management system that can measure leadership, working commitment and environment. This study aimed to analyze the correlation between leadership and working commitment or environment based on Malcolm Baldrige Criteria.Method: This was quantitative research with cross sectional design. Subjects of this study were 60 lecturers of diploma 3 midwifery in the DIY Province. The research was conducted in March-April 2011 using questionnaire based on Malcolm Baldrige Criteria. Data were analyzed by Rank Spearman and Chi Square with level of significant p<0,05.Results: There was positive correlation between leadership and working commitment (rs=0,740, p<0,001). Leadership has a positive correlation with working environment (rs=0,719 and p<0,001). The chi square result of leadership and working commitment and environment corellation shows p value<0,001. The more effective the leadership the higher the working commitment and environment would be. Age and work experience had no correlation with variables in this study. there were no difference between respondent who are married and unmarried regarding all variables.Conclusion: Based on Malcolm Baldrige Criteria, leadership has positive correlation with lecturer’s working commitment and environment.